2020
DOI: 10.1093/jac/dkaa468
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and dosing optimization of azlocillin in neonates with early-onset sepsis: a real-world study

Abstract: Objectives Nowadays, real-world data can be used to improve currently available dosing guidelines and to support regulatory approval of drugs for use in neonates by overcoming practical and ethical hurdles. This proof-of-concept study aimed to assess the population pharmacokinetics of azlocillin in neonates using real-world data, to make subsequent dose recommendations and to test these in neonates with early-onset sepsis (EOS). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In a recent phase II clinical trial of azlocillin in preterm and term infants ≤ 72 h old, Wu et al conducted Monte Carlo simulations with a desired target of 70% f T> MIC up to 32 mg/L. The authors showed that increasing the frequency (100 mg/kg every 8 h) achieved the target in 91.2% of infants compared to 63.1% of PTA with 100 mg/kg, every 12 h, both with a 0.5 h infusion ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent phase II clinical trial of azlocillin in preterm and term infants ≤ 72 h old, Wu et al conducted Monte Carlo simulations with a desired target of 70% f T> MIC up to 32 mg/L. The authors showed that increasing the frequency (100 mg/kg every 8 h) achieved the target in 91.2% of infants compared to 63.1% of PTA with 100 mg/kg, every 12 h, both with a 0.5 h infusion ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 Although well documented in adults, PK and PD of these antibiotics are poorly explored in critically ill neonates; the sparsity of studies suggests that current dosing is frequently inadequate. [59][60][61] Therefore, there is an urgent need to characterize a population PK of commonly used beta-lactams in neonates associated with target attainment to develop evidence-based dosing schemes and TDM practices. Recently, population PK models for the penicillins, amoxicillin, piperacillin, azlocillin, and the cephalosporin cefathiamidine have been developed and used to calculate target attainment with present SmPC and local dosing schemes.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…To ensure that the finding of this trial can comprehensively reflect PD characteristics of latamoxef in EONS treatment, 70% fT > MIC will be used as the primary outcome indicator, and efficacy and safety indexes will be employed as the secondary outcome indicators. Because there’s no clinical evaluation of latamoxef in EONS treatment, the trial design is derived from other clinical trials about cephalosporin treatment or therapeutic decision conducted in children or neonates ( Stocker et al, 2017 ; Wu et al, 2020 ). Rate of treatment failure, duration of antibiotic therapy, changes of inflammatory indicators, results of blood culture and incidence of AEs are commonly used indicators in efficacy and safety evaluation for anti-infective agents ( Molyneux et al, 2011 ; Stocker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome will be 70% fT > MIC, which is the target rate of 70% of patients having a free antimicrobial drug concentration exceeding the MIC during 70% of the dosing interval. 70% fT > MIC is appropriate to evaluate therapeutic efficacy of time dependent antibiotics in neonates ( Craig, 1995 ; Wu et al, 2020 ). Based on PPK model of latamoxef, 70% fT > MIC will be calculated after testing plasma drug concentration at the initial stage of treatment ( Table 3 ).…”
Section: Methods and Designmentioning
confidence: 99%